2016
DOI: 10.1038/srep37865
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and drug resistance of Clostridium difficile infection in Mainland China: a systematic review and meta-analysis

Abstract: It has been widely reported that the incidence and severity of Clostridium difficile infection (CDI) have increased dramatically in North America and Europe. However, little is known about CDI in Mainland China. In this study, we aimed to investigate the incidence of CDI and the main epidemic and drug-resistant strains of C. difficile in Mainland China through meta-analysis of related studies published after the year 2010. A total of 51 eligible studies were included. The pooled incidence of toxigenic C. diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
8
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 51 publications
6
47
8
2
Order By: Relevance
“…To reveal the epidemiology of CDI in mainland China, in this non-outbreak situation, specific genotypes of toxigenic C. difficile strains were observed. ST2 was the most predominant genotype, while recent studies reported that ST54, ST3 and ST37 were the most prevalent genotypes in mainland China [6,33,[36][37][38]. Noteworthily, in addition to ST54 and ST3, ST35 also emerged both in this work and another inspection in Yunnan [39], a province bordering Chongqing, witnessing the spread of this toxin genotype over provinces in China.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…To reveal the epidemiology of CDI in mainland China, in this non-outbreak situation, specific genotypes of toxigenic C. difficile strains were observed. ST2 was the most predominant genotype, while recent studies reported that ST54, ST3 and ST37 were the most prevalent genotypes in mainland China [6,33,[36][37][38]. Noteworthily, in addition to ST54 and ST3, ST35 also emerged both in this work and another inspection in Yunnan [39], a province bordering Chongqing, witnessing the spread of this toxin genotype over provinces in China.…”
Section: Discussionsupporting
confidence: 51%
“…Geographical heterogeneity and transcontinental dissemination have aroused more concerns about regional CDI surveillance. In China, although the state of dilemma introduced by CDI has been documented before [6,7], data are lacking in the central and western regions. To fill gaps in the epidemiological territory of CDI in China, the results in this study presented basic knowledge of the prevalence and mortality of HA-CDI, and helped to improve the recognition of patients at high risk for HA-CDI Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon initiation of antibiotic therapy, the normal gut flora was disrupted, enabling C. difficile to persist in the gut as the dominant bacteria and induce colitis [66,67]. Keeping in mind that virulence if often tied to resistance [68], the emergence of highly virulent strains of this bacteria and a reduced susceptibility to antibiotics has led to the development of MDR strains [69].…”
Section: Targeted Drug Delivery Systemsmentioning
confidence: 99%